2014
DOI: 10.1186/1556-276x-9-590
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of titanium nitride for self-aligned gate AlGaN/GaN heterostructure field-effect transistors

Abstract: In this study, titanium nitride (TiN) is synthesized using reactive sputtering for a self-aligned gate process. The Schottky barrier height of the TiN on n-GaN is around 0.5 to 0.6 eV and remains virtually constant with varying nitrogen ratios. As compared with the conventional Ni electrode, the TiN electrode presents a lower turn-on voltage, while its reverse leakage current is comparable with that of Ni. The results of annealing evaluation at different temperatures and duration times show that the TiN/W/Au g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The AlGaN/GaN HEMTs with TiN-based gate have been demonstrated by other groups. [11][12][13][14][15] However, these works mainly focused on the improvement of device characteristics such as current collapse, 14 thermal stability, [11][12][13]15 and high voltage stress effect. 15 Recently, we have also reported an improved Schottky barrier height (SBH) of $1.1 eV in AlGaN/GaN HEMTs with sputtered TiN as the gate electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AlGaN/GaN HEMTs with TiN-based gate have been demonstrated by other groups. [11][12][13][14][15] However, these works mainly focused on the improvement of device characteristics such as current collapse, 14 thermal stability, [11][12][13]15 and high voltage stress effect. 15 Recently, we have also reported an improved Schottky barrier height (SBH) of $1.1 eV in AlGaN/GaN HEMTs with sputtered TiN as the gate electrode.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Schottky (SC) emission was realized in n-type Ge substrates with Pt 18 and Se 19 Schottky contacts, and Poole-Frenkel (PF) emission was widely adopted for the III-nitrides (GaN, 20 AlGaN/ GaN, [20][21][22] and AlInN/GaN 22,23 ) with Ni-based Schottky contacts by electron beam (e-beam) evaporation. However, TiN gate was commonly deposited by the sputtering process, [11][12][13][14][15][16][17] which may lead to plasma damages to the surface of the AlGaN/GaN HEMT structure. Hence, it is important to study and understand the gate leakage current mechanism of AlGaN/ GaN SBDs and HEMTs with sputtered TiN.…”
Section: Introductionmentioning
confidence: 99%
“…However, the work temperature is only tested to 200 °C. In our previous work, we have confirmed that TiN/GaN Schottky contact presented good rectification characteristics after 850 °C annealing for 10 minutes [29][30][31]. Therefore, we believe that the TiN anode GaN SBD has the potential to sense higher temperatures (T>600 K).…”
mentioning
confidence: 63%
“…These latter (TaN and TiN) exhibited some interesting features, such as a low leakage current combined with a good thermal stability [23,24]. The electrical properties of these systems are strongly influenced by the deposition technique, as their work function can vary in wide range (i.e., 4.13 -5.05 eV for TaN [26] and 3.8 -4.6 eV for TiN) [27,28,29].…”
Section: Introductionmentioning
confidence: 99%